Respuestas

2013-10-28T04:06:47+01:00
1+senx+ senx/cosx) / ( 1+cosx + cosx/senx) =k

(( Cosx+senxcosx + senx) / cosx ) / ( senx + cosx senx + cosx) / senx ) = k.

Senx/ cosx = k

Tan(x)= k

Ahora resolvemos el otro problema:

(Sec x - cos x ) / (csc x - sen x )

( ( 1/ cosx - cosx ) / (1/senx - senx ) )

(( 1- cos^2 (x) / cosx ) / (1-sen^2(x) / senx ) )

((Sen^2 ( x)/ cosx ) / ( cos^2 ( x ) / sen x ))

Sen^3 ( x ) / cos^3 (x) = tan^3 (x)

Del primer ejercicio sacamos el valor de k

Tanx = k

Entonces:

Tan^ 3 ( x ) = k ^3

Espero que te sirva de ayuda